2022
DOI: 10.1088/1361-648x/ac6787
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic structure of DyFeO3 revisited: Fe spin reorientation and Dy incommensurate magnetic order

Abstract: High resolution and high intensity neutron powder diffraction is used to study the ground state magnetic order and the spin reorientation transition in the orthoferrite DyFeO3. The transition from the high temperature k =0 Γ4 (GxAyFz) to the low temperature Γ1 (AxGyCz) type order of the Fe-sublattice is found at TSR= 73 K and does not show any thermal hysteresis. Below TN2 = 4 K the Dy-sublattice orders in an incommensurate magnetic structure with k = [0, 0, 0.028] while the Fe-sublattice keeps its commensurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…We note that a similar field-induced incommensurate magnetic order with k = (0 0 1 ± δ) was observed previously in the isostructural material YbAlO 3 [44,45]. Moreover, very recently an incommensurate order (SDW or eliptical spiral) with k = (0 0 1 ± δ) was reported in another isostructural compound DyFeO 3 [26,27], where it could be related with interaction between Fe and Dy magnetic subsystems. Lowtemperature in-field neutron diffraction measurements would be required to verify the presence of the incommensurate field-induced magnetic phases in DyScO 3 .…”
Section: Monte Carlo Simulationssupporting
confidence: 84%
See 1 more Smart Citation
“…We note that a similar field-induced incommensurate magnetic order with k = (0 0 1 ± δ) was observed previously in the isostructural material YbAlO 3 [44,45]. Moreover, very recently an incommensurate order (SDW or eliptical spiral) with k = (0 0 1 ± δ) was reported in another isostructural compound DyFeO 3 [26,27], where it could be related with interaction between Fe and Dy magnetic subsystems. Lowtemperature in-field neutron diffraction measurements would be required to verify the presence of the incommensurate field-induced magnetic phases in DyScO 3 .…”
Section: Monte Carlo Simulationssupporting
confidence: 84%
“…However, very recently a highresolution neutron diffraction study reported incommensurate elliptical spiral or spin density wave (SDW) order of Dy moments with k = (0 0 1 ± δ). Such an incommensurate magnetic structure could potentially have an impact on the dielectric response of DyFeO 3 due to lowering of the symmetry [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth orthoferrites (RFeO 3 ) have a distorted perovskite structure with a space group of Pbnm . As a functional material family, RFeO 3 attracts great scientific interest and has technological significance for potential applications such as magneto-optical switch, ultrafast optomagnetic recording, precession excitation induced by terahertz pulses, and magnetism-induced ferroelectric multiferroics. Their abundant magnetic properties mainly originate from 3d-electrons of Fe 3+ and 4f-electrons of R 3+ . , The two magnetic ions (R 3+ and Fe 3+ ) form in three types of magnetic sublattices, including Fe 3+ –Fe 3+ , Fe 3+ –R 3+ , and R 3+ –R 3+ sublattices . The strongest one of those is Fe 3+ –Fe 3+ with G-type antiferromagnetic interaction, which causes the iron ions to orient opposite to all nearest neighbors in three dimensions below the first Neel temperature at 650–700 K. The presence of a Dzyaloshinskii–Moriya interaction induces an asymmetric electronic exchange, resulting in a spontaneous magnetization in the c -axis of a RFeO 3 single crystal below the Neel temperature.…”
Section: Introductionmentioning
confidence: 99%